Proximate and Mineral Composition of Boiled Carnavalia ensiformis Seeds - Akingbade, A.A.; Sodeinde, F.G.; Olaniy, C.O.; Oyetayo, O.S.; Fadare, O.R.; Rabiu, A.O. (Pakistan Journal of Nutrition, 2009)
The study examines the proximate and mineral composition of Carnavalia ensiformis seeds subjected to varying periods of boiling in water. There were four treatments, which comprised: 1 hr, 2 hrs, 3 hrs and 4 hrs water boiling. Each treatment was made up of three replicates. After the expiration of each boiling period, the water was discarded, sun-dried for 7 days and thereafter milled to pass through 1 mm sieve and subjected to laboratory analysis. The study revealed the following: Dry matter did not differ significantly, P < 0.01, across treatments. Crude protein recorded for the 4 hrs boiling had a higher value of 21%. Highest crude fibre was recorded for the 2 hrs boiling. Ether extract decreased in value up to the 3 hrs treatment time but later increased in seeds boiled for 4 hrs. Ash content decreased from 4% in the raw seeds to 2% after boiling for 2 hrs but later increased to 4% in seeds subjected to 4 hrs boiling. Magnesium level increased to 20% in seeds boiled for 3 hrs but zinc level decreased from 0.73% in the raw seeds to 0.42% in seeds subjected to 4 hrs of boiling. Iron content recorded a decrease at 3 hrs of boiling but boiling for 4 hrs recorded an increase while copper content recorded an increase in seeds boiled for 3 hrs. The results revealed that subjecting seeds of Canavalia ensiformis to 4 hrs boiling in water led to a release more nutrients in improve form.